1993
DOI: 10.1007/bf00225036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of apple cultivars using RAPD markers

Abstract: Eleven apple cultivars were differentiated using randomly amplified polymorphic DNA (RAPD) markers obtained by the polymerase chain reaction (PCR). The variability of the technique and of the origin of the DNA extract was analyzed. A set of bands consistent in their presence or absence was chosen to create a differentiating band pattern. A key is proposed by which one can differentiate apple cultivars using commercially available prime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0
7

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(83 citation statements)
references
References 11 publications
2
73
0
7
Order By: Relevance
“…This confirms the usefulness of RAPD markers for fingerprinting purposes suggested in many previous studies (e.g. Koller et at., 1993;Keil & Griffin, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…This confirms the usefulness of RAPD markers for fingerprinting purposes suggested in many previous studies (e.g. Koller et at., 1993;Keil & Griffin, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…[147,159] This could also be used in the study of genotype identification. [160][161][162] In another study, Sasaki and Nagumo reported rapid identification of C. longa and C. aromatica by LAMP method. [163] A study conducted by Sigrist et al showed genetic diversity of turmeric germplasm (C. longa; Zingiberaceae) using microsatellite markers to discover genetics and molecular research.…”
Section: Molecular Marker Analysis Inmentioning
confidence: 99%
“…Both RAPD and IS-SR marker, based on PCR techniques have proven to be a reliable, easy to generate, inexpensive and versatile set of marker that rely on repeatable amplification of DNA se-quence using single primers. The RAPD and ISSR markers can be used in the study of the genetic variability of species or natural populations and in the identification of genotypes [7][8][9][10][11][12][13][14]. In this communication, we report the feasibility of PCR-based DNA (RAPD and ISSR) marker for phylogeny study and identification for conservation of Phyllanthus species.…”
Section: Introductionmentioning
confidence: 99%